Serum Systemic Autoantibodies in Anti-N-Methyl-D-Aspartate Receptor Encephalitis - Zhang, Bingjun; Yang, Yu; Lin, Yinyao; Ai, Lulu; Men, Xuejiao; Lu, Zhengqi (Frontiers in Neurology, 2020)
Objective The aim of this retrospective study was to investigate the relationship between serum systemic autoantibodies and anti-N-methyl-D-aspartate receptor (NMDAR) encephalitis. Methods Thirty-nine patients with anti-NMDAR encephalitis were examined for serum systemic autoantibodies (antinuclear antibodies, extractable nuclear antigen autoantibodies, rheumatoid factors, and anti-neutrophil cytoplasmic antibodies), in comparison with 39 neuromyelitis optica spectrum disorder (NMOSD) and 78 healthy controls. Clinical features, cerebrospinal fluid characteristics, and outcomes were compared between the two subgroups of anti-NMDAR patients with positive and negative systemic autoantibodies, respectively. Results Anti-NMDAR encephalitis patients had higher frequency of positive serum systemic autoantibodies than healthy controls (23.1% vs 2.6%, p = 0.001) and lower frequency than NMOSD (23.1% vs 48.7%, p = 0.018). No patients were diagnosed comorbidities with non-organ-specific autoimmune diseases. Consciousness disturbance was more frequent in autoantibodies positive group than in the negative group (88.9% vs 40.0%, p = 0.02). Autoantibody positive group had a poorer outcome than autoantibody negative group (55.6% vs 86.7%, p = 0.043). There was a negative correlation between serum autoantibodies and outcomes in anti-NMDAR encephalitis patients (r = -0.325, p = 0.044). Conclusion Our data demonstrated serum systemic autoantibodies were more frequent in anti-NMDAR encephalitis patients than in healthy controls and less frequent than NMOSD, which were associated with higher severity of disease.